2008
DOI: 10.1111/j.1755-053x.2008.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

How Did the 2003 Dividend Tax Cut Affect Stock Prices?

Abstract: "We test the hypothesis that the 2003 dividend tax cut boosted US stock prices and thereby lowered the cost of equity capital. Using an event-study methodology, we attempt to identify an aggregate stock market effect by comparing the behavior of US common stock prices with that of foreign equities and the equities of real estate investment trusts (REITs). We also examine the relative cross-sectional response of prices of high- and low-dividend-paying stocks. We do not find any imprint of the dividend tax cut n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…148 The weight of the evidence from the papers discussed above seems to refute the irrelevance view, however, Amromin et al (2007) question whether the 2003 tax cut in particular had any aggregate effect on prices. In addition, tax regime changes are endogenous and highly correlated with other developments in the economy, past, present and future (Romer and Romer, 2008).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…148 The weight of the evidence from the papers discussed above seems to refute the irrelevance view, however, Amromin et al (2007) question whether the 2003 tax cut in particular had any aggregate effect on prices. In addition, tax regime changes are endogenous and highly correlated with other developments in the economy, past, present and future (Romer and Romer, 2008).…”
mentioning
confidence: 86%
“…There is growing evidence that the irrelevance view does not hold and that taxes matter in the pricing of stocks. However, taxes generally appear to be capitalized at low rates in event study tests, long-run return studies depend on cross-sectional variation using a proxy of institutional ownership (discussed further below), and recent evidence in Amromin et al (2007) suggests that aggregate effects from a substantial dividend rate cut may have been trivial. While the documentation of any association between dividend taxes and returns or prices has been difficult, empirical tests to distinguish between the traditional view and the new view have been nearly impossible because of the endogenous nature of tax law changes and the fact that temporary tax law changes makes the predicted results under the new view and traditional view very similar.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on dividend tax changes has been criticised by some, as these tax changes only affected individuals who make up a minority of shareholders (Amromin et al 2008). By contrast, the South African tax change caused a tax preference for higher dividend payments amongst corporates and simultaneously introduced a tax preference for retained earnings amongst individuals.…”
Section: Dividend Taxation In South Africamentioning
confidence: 99%
“…Similarly, a number of researchers found that firms in the United States increased their dividend payments after a tax cut during 2003 (Blouin, Raedy & Shackelford 2011;Chetty & Saez 2005). By contrast, Amromin, Harrison and Sharpe (2008) contended that the 2003 dividend tax cut in the United States affected a minority of investors (i.e. individual investors).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Poterba (2004) estimates, for example, that the 2003 cuts in dividend taxation and CGT in the USA increased share prices by around 6 per cent; ex post, Amromin et al (2006) find the aggregate effect to have been muted, but with a substantial impact for high-dividend-paying firms. And there is evidence that announcements of reductions in stamp duty on share transactions in the UK have led to greater price increases for more frequently traded stocks.…”
Section: Taxation and Financial Asset Pricesmentioning
confidence: 99%